Pengaruh Intellectual Capital terhadap Kinerja Keuangan Dimoderasi Budaya Organisasi pada Industri Perhotelan yang Go-Publik di Indonesia - ratna dwi Rachmawati (Jurnal Ilmu Manajemen (JIMMU), 2020)
The tourism industry in Indonesia is currently growing very rapidly, this will have an impact on the growth in the hospitality industry that rapidly anyway. The growth in the hospitality industry will increase the intensity of the competition. The intensity of the competition which will require the support of competent human resources.  A competent human resources is the intellectual capital that improve competitiveness. The existence of cultural organizations that support the development of knowledge and skills of human resources, is very strategic. Intellectual capital will be able to improve the financial performance of the hospitality.This research aims to test the influence of intellectual capital on performance corporate hospitality. In addition the study also tested the influence of intellectual capital on performance by adding a variable hospitality company organizational culture as moderation. This research uses data panel (includes time series data and cross section) that includes eight samples the hospitality industry during the years 2012-2015. A method of data analysis in this study uses the approach of Partial Least Squares (PLS).Research results revealed that Intellectual Capital effect significantly to financial performance, but the culture of the organization is not able to strengthen or weaken the influence of Intellectual Capital (VAIC ™) against the financial performance of the company's hospitality. Keywords: Intellectual Capital, financial performance, organizational culture.